Repurposing the Veterinary Antibiotic Apramycin for Antibacterial and Antibiofilm Activity Against Pseudomonas aeruginosa From Cystic Fibrosis Patients - Di Bonaventura, Giovanni; Lupetti, Veronica; Verginelli, Fabio; Giancristofaro, Sara; Barbieri, Rosemary; Gherardi, Giovanni; Pompilio, Arianna (Frontiers in Microbiology, 2022)
Objectives: To evaluate the in vitro antibacterial, antibiofilm, and antivirulence activities of apramycin, comparatively to tobramycin, against a set of P. aeruginosa from chronically infected cystic fibrosis (CF) patients. Methods The activity of antibiotics against planktonic cells was assessed by performing MIC, MBC, and time-kill assays. The activity against mature biofilms was evaluated, in a microtiter plate, both in terms of dispersion (crystal violet assay) and residual viability (viable cell count). The effect of drug exposure on selected P. aeruginosa virulence genes expression was assessed by real-time Reverse Transcription quantitative PCR (RT-qPCR). Results Apramycin MIC90 and MBC90 values were found at least fourfold lower than those for tobramycin. A comparable trend was observed for mucoid strains. Only 4 out of 24 strains (16.6%) showed an apramycin MIC higher than the epidemiological cut-off value of 64 mg/L, whereas a higher resistance rate was observed for tobramycin (62.5%; p < 0.01 vs. apramycin). In time-kill analyses, both aminoglycosides were found bactericidal, although apramycin showed a more rapid effect and did not allow for regrowth. Apramycin generally stimulated biofilm biomass formation, whereas tobramycin showed opposite trends depending on the strain tested. Both drugs caused a highly significant, dose-dependent reduction of biofilm viability, regardless of strain and concentration tested. The exposure to apramycin and tobramycin caused increased expression of mexA and mexC (multidrug efflux pumps), whereas tobramycin specifically increased the expression of aprA (alkaline protease) and toxA (exotoxin A). Neither apramycin nor tobramycin showed cytotoxic potential toward IB3-1 bronchial epithelial CF cells. Conclusion Our results warrant future pharmacokinetic and pharmacodynamic studies for supporting the rationale to repurpose apramycin, a veterinary aminoglycoside, for CF lung infections.